Characterization of physico-chemical features of terung asam Sarawak (Solanum lasiocarpum Dunal) fruit during growth, maturation and ripening - Ting, Albert Koon Soon (2021)
A study on characterizing the changes in physico-chemical, antioxidant activities and cellular structure of “terung asam Sarawak” fruit was conducted on weekly intervals from anthesis until fruit senescence. In this study, fully bloomed flowers of “terung asam” plant were tagged and the fruits were thinned to allow only one per cluster. The experiment was conducted by using a completely randomized design with twelve fruit replications for each week after anthesis (WAA). Logistic regression analysis was used to analyse morphological traits (fruit length, diameter, fresh weight and volume). Data from measurements of respiration rate and ethylene production, colour, moisture content, firmness, soluble solids concentration (SSC), pH, titratable acidity (TA), total phenolic content, total carotenoid content and antioxidant activities were analysed by using analysis of variance whereas means were separated by Duncan’s multiple range test (DMRT). Light microscopy (LM) and scanning electron microscopy (SEM) were utilized to document “terung asam” fruit’s growth at the cellular level. Results illustrated that “terung asam” fruit took about 115 days or 16 weeks from anthesis until ripening. The fruit exhibits a single sigmoid growth pattern where three physiological stages (S1, S2 and S3) were identified. At S1, cells of “terung asam” fruit went through rapid division, followed by cell expansion at S2 before reaching physiological maturity at S3. These changes were in accordance with cellular structure as observed under LM and SEM. “Terung asam” fruit appeared green in colour at the initial growth stage before it became yellow then orange at later weeks. The visual colour changes of “terung asam” fruit were tally with L*, a* and b* values as fruit matured and ripened. Fruit firmness increased initially and then decreased during ripening whereas SSC and TA increased gradually as WAA progressed. In contrast, fruit pH decreased gradually as WAA progressed. As “terung asam” fruit matured and ripened, citric acid increased but succinic acid decreased. On the other hand, malic acid increased as fruit matured but decreased when fruit ripened. Respiration and ethylene production rate of “terung asam” fruit were high at the initial stage of growth then reduced and remained constant at later stages. As for total carotenoid content, it was initially low in concentration and the carotenoid pigments started to accumulate as the fruit reached maturity and achieved the highest amount when fruit reached 16 WAA. Total phenolic content decreased at the early growth stage then started to increase as the fruit reached maturation and dropped again as the fruit reached 16 WAA. “Terung asam” fruit at 13 until 15 WAA displayed the highest amount of antioxidant activities, total phenolic content and vitamin C. “Terung asam” fruit’s vitamin C at ripening stage can reach about 3 to 4 folds more than that of guava (Psidium guajava L.) fruit. Results from the current study concluded that “terung asam” fruit harvested at 14 WAA could be determined as optimum harvest maturity when the fruit has developed good organoleptic (firmness, moisture, SSC, TA, organic acids, etc.) and quality attributes (vitamin C, carotenoid content, phenolic content and antioxidant activities) during ripening. Since “terung asam” fruit is a promising fruit by having a high amount of vitamin C and total phenolic content (TPC), this fruit need to be intensively commercialized for fruit and food industries to explore and utilize “terung asam” fruit to its full potential. All in all, the physico-chemical, antioxidant activities and cellular structure of “terung asam” fruit changed as it grew, matured and ripened.